Healthcare Logistics & Supply Chain Management in Health Industry of Indonesia Based on the Telemedicine - Carolina Kuntardjo (International Journal of Supply Chain Management, 2020)
Abstract— The essential mission of logistics and supply chain management is to efficiently plan, organize, and coordinate the movement of goods from a point of origin to a point of consumption. Analyzing and aligning supply chain goals with a patient-first approach enables healthcare organizations to reduce costs while improving patient outcomes. With Patient Direct, a care delivery solution from HRS, this paper provides patients with the telehealth equipment they need when they need it by telemedicine. Telemedicine which is used interchangeably with the term telehealth is the remote delivery of healthcare to patients through information and communication technology, including communication between two or more health professionals who are not in the same location. Thus, it needs secure transmission of medical data through text, sound, image, or video. This system can be a tele-education, tele-monitoring, tele-consultation, or tele-intervention. Telemedicine has several benefits, both for health professionals and medical institution as well as for the patients, especially for the development of healthcare delivery in remote area and also to make interaction between healthcare professional faster. However, telemedicine still has lack of regulation in Indonesia. There is still no regulation about license for the health professional and safety of medical data. Ethical problems in telemedicine are also still an issue, especially about patient’s confidentiality, and also it can weaken doctor-patients relationship. According code of ethics, a doctor must examine the patients first before making a diagnosis and treatment, which cannot be done with telemedicine. The lack of regulation and ethical consideration make telemedicine in Indonesia still has some problems and need a challenge for improvement.